Untangling Real Gravity - Franc Klaassen; Rutger Teulings (Tinbergen Institute, 2017)
We derive a real gravity equation and gain several new insights that were hidden in the nominal specification used so far. Most importantly, the real effective exchange rate (REER) of the exporter and, via the importer's terms of trade, also the importer's REER matter, and we can identify the elasticity of substitution. We estimate real gravity for 18 OECD countries. Therefore, we extend the untangling normalization method from an “it” to an “ijt” panel data model and use it to exploit all variables proposed by theory, despite a broad set of fixed effects (FE). We find that both REERs are important and estimate an elasticity of substitution of 1.5. If we assume homogeneous parameters, as is common, the remaining unexplained exporter-time and importer-time deviations are still substantial, relaxing this assumption improves this. We now explain 64 and 70% of the exporter-time and importer-time deviations, respectively, and thus the majority of the exporter and importer multilateral resistances. Untangling normalization helps to get a better view of what is still unexplained by theory.
Keywords: C18; F10; F14; 330; real gravity equation; exchange rate; multilateral trade resistance; untangling normalization